Sterols and Triterpenes From the Fruit of Annona muricata Linn. - Ragasa, Consolacion Y.; Torres, Oscar B.; Soriano, Geneveve; Shen, Chien-Chang (Silliman Journal, 2022)
Annona muricata Linn., commonly known as guyabano, is a wellknown medicinal tree. The bioactivities of A. muricata are varied, but the commonly isolated compounds are acetogenins which exhibit anticancer properties. This study reports on the isolation of the sterols: β-sitosterone (1), β-sitosteryl fatty acid ester (2) and β-sitosterol (3); and the triterpenes: β-amyrin (4), β-amyrin (5) and squalene (6) from the dichloromethane extract of the freeze-dried fruit of Annona muricata Linn. Compounds 1-6 were isolated by silica gel chromatography and identified by NMR spectroscopy. These compounds were reported to possess diverse bioactivities.